Assessment of Controlled Substance Distribution to U.S. Veterinary Teaching Institutions From 2006 to 2019 - Piper, Brian J.; McCall, Kenneth L.; Kogan, Lori R.; Hellyer, Peter (Frontiers in Veterinary Science, 2020)
Objective: To evaluate the changing pattern of distribution of Schedule II and III opioids, barbiturates, and stimulants to veterinary educational institutions in the United States. Design: Longitudinal study. Sample: Veterinary teaching institutions that use Schedule II and III drugs. Procedures: Distribution of controlled substances to veterinary teaching institutions was obtained from the Drug Enforcement Administration’s Automated Reports and Consolidated Orders System (ARCOS) for opioids (e.g. methadone, fentanyl, codeine), barbiturates (pentobarbital, butalbital), and stimulants (amphetamine, methylphenidate, lisdexamfetamine) from 2006 - 2019. Opioids were converted to their morphine milligram equivalents (MME) for evaluation over time. Results: Controlled substance distribution to veterinary schools exhibited dynamic, and agent specific, changes. The total MME for eleven opioids peaked in 2013 and decreased by 17.3% in 2019. Methadone accounted for two-fifths (42.3%) and fentanyl over one-third (35.4%) of the total MME in 2019. Pentobarbital distribution was greatest by weight of all substances studied and peaked in 2011 at 69.4 kg. Stimulants underwent a pronounced decline and were very modest by 2014. Conclusions and Clinical Relevance: Opioids by total MME in veterinary teaching practice have undergone more modest changes than opioids used with humans. Hydrocodone, codeine and recently fentanyl use have declined while methadone increased. Stimulant distribution decreased to become negligible. Together, this pattern of findings warrant continued monitoring.